MUTILATION OF THE INDEPENDENCE OF THE JUDICIARY: THREATS, INTIMIDATION AND CONSTITUTIONAL AMENDMENTS IN ZIMBABWE - Tembo, Simbarashe; Singh, Annette (Obiter, 2023)
Zimbabwe adopted a new Constitution in 2013. It was widely believed that the new Constitution would deepen democracy and constitutionalism. Central to this was the establishment of an independent judiciary. Barely 10 years after the adoption of the Constitution, judicial independence has deteriorated. This has been the result of intimidation against the judiciary, and constitutional changes aimed at weakening the judiciary. This article is intended to show that there exists a long-term project to bring the judiciary under the control of the political arms in Zimbabwe. With a weakened judiciary, Zimbabwe loses the chance to entrench constitutionalism, democracy and the rule of law. The article first highlights the imperative of judicial independence, then examines how the judiciary has suffered from threats at the hands of politicians, and finally assesses the impact of two recent constitutional amendments on the independence of the judiciary. It is shown that the independence of the judiciary has been systematically mutilated, and that hopes for effective judicial review cardinal to constitutionalism have waned.